2019
DOI: 10.1109/tit.2018.2885782
|View full text |Cite
|
Sign up to set email alerts
|

Matched Metrics to the Binary Asymmetric Channels

Abstract: In this paper we establish some criteria to decide when a discrete memoryless channel admits a metric in such a way that the maximum likelihood decoding coincides with the nearest neighbor decoding. In particular we prove a conjecture presented by M. Firer and J. L. Walker establishing that every binary asymmetric channel admits a matched metric. Index TermsBinary asymmetric channel, channel model, maximum likelihood decoding I. INTRODUCTIONAs it is well known, maximum likelihood decoding (MLD) over a symmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Shortly after that, Qureshi showed that the binary asymmetric channel admits a matched metric [10], establishing a conjecture of Firer and Walker [6]. The approach of [10] develops criteria (and algorithms) to understand when a discrete memoryless channel admits a metric for which the maximum likelihood decoder coincides with the nearest neighbour decoder. A current open problem is to explicitly describe the metrics matching the binary asymmetric channel.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Shortly after that, Qureshi showed that the binary asymmetric channel admits a matched metric [10], establishing a conjecture of Firer and Walker [6]. The approach of [10] develops criteria (and algorithms) to understand when a discrete memoryless channel admits a metric for which the maximum likelihood decoder coincides with the nearest neighbour decoder. A current open problem is to explicitly describe the metrics matching the binary asymmetric channel.…”
Section: Introductionmentioning
confidence: 96%
“…In 2016 it was proved in [9] that the binary asymmetric channel is metrizable in the weak sense of Massey [8]. Shortly after that, Qureshi showed that the binary asymmetric channel admits a matched metric [10], establishing a conjecture of Firer and Walker [6]. The approach of [10] develops criteria (and algorithms) to understand when a discrete memoryless channel admits a metric for which the maximum likelihood decoder coincides with the nearest neighbour decoder.…”
Section: Introductionmentioning
confidence: 99%
“…Further researches on "Matched " metric Figure 2. Binary asymmetric memoryless channel ( [13], [19], [20]) to focus the ability on the usual decoding algorithms (the maximum likehood decoding and nearest neighbour decoding ) for CN codes. In [6], the authors suggested and discussed two kinds of metrics for CN codes.…”
Section: Introductionmentioning
confidence: 99%